Nanoscale imaging of hydrogen and sodium in alteration layers of corroded glass using ToF‐SIMS: Is an auxiliary sputtering ion beam necessary?. (11th October 2018) - Zhang, Jiandong; Zhang, Yanyan; Collin, Marie; Gin, Stephane; Neeway, James J.; Wang, Tieshan; Zhu, Zihua
Abstract : The hydrogen (H)/sodium (Na) interface is of great interest in glass corrosion research. Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) is one of the few techniques that can provide nanoscale H and Na imaging simultaneously. However, the optimized condition for ToF‐SIMS imaging of H in glass is still unclear. In H depth profiling using ToF‐SIMS, H background control is a key, in which an analysis ion beam and a sputtering ion beam work together in an interlaced mode to minimize it. Therefore, it is of great interest to determine if an auxiliary sputtering ion beam is also necessary to control H background in ToF‐SIMS imaging of H. In this study, H imaging with and without auxiliary sputtering beams (Cs +, O2 +, and Arn + ) was compared on a corroded international simple glass (ISG). It was surprising that the H/Na interface could be directly imaged using positive ion imaging without any auxiliary sputtering ion beam under a vacuum of 2 to 3 × 10 −8 mbar. The H + background was about 5% atomic percent on the pristine ISG glass, which was significantly lower than the H concentration in the alteration layer ( 15%). Moreover, positive ion imaging could show distributions of other interesting species simultaneously, providing more comprehensive information of the glass corrosion. If an auxiliary O2 + sputtering ion beam was used, the H + background could be reduced but still higher than that in the depth profiling. Besides, this condition could cause significant loss of signal intensities due to strong surface charging.